The PPR, Systemic Transformation, and New Poland. Opportunity Structures in the Biographical Experience of Senior Social Reformers - Golczyńska-Grondas, Agnieszka (Qualitative Sociology Review, 2019)
The paper is based on preliminary results of the analysis of four pilot narrative autobiographical interviews conducted with members of the oldest generation of Polish social innovators (born in the 1930s—early 1950s) working in the human sector area CSOs. In this text, I use the concept of opportunity structures, reflecting over sets of structures which facilitate the professional and personal development of social reformers. I refer mainly to Institutional Opportunity Structures emerging in Poland under the socialist regime, during and post systemic transformation. The leading argument here is that the social innovator’s career interrelates with the use of opportunity structures available in a political and economic system regardless of its type and prevalent ideology.